Elaboración de campaña publicitaria y mejoramiento de imagen corporativa de la mecánica indusrtial EL ENGRANAJE ubicada en la parroquia Venús del Río Quevedo, periodo 2015 - Montiel Bravo, Sabrina Lorena (2015)
This research has developed an advertising campaign and improvement of corporate image for "El Engranaje" Industrial Mechanic located in the Venus del Río Quevedo Parish, it appears as an alternative to deal to give solution to the problem which is lack of advertising that does not allow to publicize the existence of the company as well as its products and services within the industrial market and at the same time the lack of a striking corporate image that is positioned in the minds of consumers. Based on the results of the surveys carriet out, it could determined that 83% of the survery respondents do not know “El Engranaje” the Industrial Mechanics, these results allowed develop Media Plan, also allowed to establish objectives and advertising strategies that were applied at the time of broadcast advertising campaign and at the same time for the redesign of the corporate image of the company. Once defined advertising strategies was a budget for the dissemination of advertisements in the mass media (Radio, newspaper, magazine and print media), in addition to the budget for prints of the artwork. To complement its development methodology was directed to the following types of research: diagnosed, field, documentary, which was made using the techniques of survey and interviews the methods of direct observation, inductive, deductive based on primary and secondary sources. Key words: Advertising, image, media.